Direct molecular approach to monitoring bacterial colonization on vacuum-packaged beef - Fontana, Cecilia Alejandra (2006)
Denaturing gradient gel electrophoresis allowed us to monitor total bacterial communities and to establish a pattern of succession between species in vacuum-packaged beef stored at 2 and 8°C for 9 weeks and 14 days. Species-specific PCR was used to confirm the presence of Lactobacillus sakei and Lactobacillus curvatus. Multiplex PCRs using 16S rRNA-specific primers allowed differentiation between Leuconostoc species. These methods provided the desired information about microbial diversity by detecting the main microorganisms capable of colonizing this ecological niche. Copyright © 2006, American Society for Microbiology. All Rights Reserved.